The analysis of the notions of Russian school principals about digital transformation - A. A. Deryabin; I. E. Boytsov; A. A. Popov; P. D. Rabinovich; K. E. Zavedensky; I. S. Tsarkov (Russian State Vocational Pedagogical University, 2021)
Introduction. The challenge of the pandemic forced educational organisations in Russia to resort to massive transition to distance learning and accelerated digital transformation of schools. It has become more obvious than ever that the digital transformation of a school is not limited to a simple technical update of its information resources but implies a fundamental rethinking of the school activities based on the capabilities of digital technologies.The aim of the study was to investigate the experience of digital transformation and the Russian school principals' notions about it as a systemic process. The subject of the study is the notion about the systemic impact of digital transformation processes on schools; the experience of complexity in the introduction of information technologies in the educational process and school management, the assessment of the progress of digitalisation; the notions about the factors of successful digital transformation, which require a critical understanding of the experience of implementing information technologies in the school, highlighting key success factors.Methodology and research methods. The authors analysed 7189 questionnaires using computer methods for processing the natural language. The questionnaires were completed in general education organisations of 66 regions from all federal districts of Russia. The respondents' answers were categorised in accordance with the European Framework for Technologically Competent Educational Organisations (DigCompOrg).Results. The research findings demonstrated the significant imbalance in the frequency of responses: the most frequent answers belong to the "Infrastructure" category, while the least frequent ones belong to the categories of pedagogical aspects of digital transformation affecting changes in the educational content and methods for assessing educational outcomes. It is concluded that the respondents' replies reflect the institutional position of school principals in the current educational system: a head of a government-funded school positions herself/himself as an administrative executor and a representative of the founder, rather than a leader of the teaching team. Consequently, the provision of educational achievements and students' personal development are largely not perceived by principles of Russian schools as a priority management task.Scientific novelty of the present research lies in the attempt to answer the question of how systematically the digital transformation of the principle is perceived, to apply DigCompOrg to the assessment of these categories by the European Framework of technologically competent educational organisations, as well as to use natural language processing methods to process text answers to open-ended questions of the questionnaire, which made it possible to obtain results on a large sample with wide geographical coverage.Practical significance. The research findings can be used in the development and implementation of advanced training programmes for school and college administrations in accordance with the ongoing digitalisation of Russian educational system.